Relaxation techniques in sports: A systematic review on acute effects on performance - Pelka, M.; Heidari, J.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M. (Performance Enhancement & Health, 2016)
Objectives: The aim was to provide an overview on the current state of research on acute effects of relaxation techniques in sports. Design: A systematic review of randomized controlled trials was conducted. Methods: PubMed, MEDLINE, PsycINFO, and SPORTDiscus were searched until August 2014. Additionally, reference lists of retrieved articles and relevant reviews were hand searched. To be included articles had to examine the effects of relaxation techniques on performance in sports. Furthermore, they had to be published in English, in a peer-reviewed journal, available full text online, and designed as either treatment outcome, clinical trial, and/or randomized controlled trial. The dependent variable had to be a measure of athletic performance. Results: Of the 8,501 articles retrieved after the databased literature search, 21 studies were included in the systematic review. Nine trials dealt solely with somatic relaxation techniques, five with cognitive techniques, and seven trials examined both branches within single studies. Biofeedback and hypnosis were found to be the most effective techniques over a range of performance measures. Conclusions: This review showed that biofeedback and hypnosis can positively influence performance throughout different outcome variables consistently. On the contrary, other techniques that were proven effective in clinical environments did not show consistent results. However, results have to be treated with caution because of considerable lack of quality of some of the trials. Future studies need to consider the methodological flaws as well as the highly individual nature of relaxation techniques.